Migrating from Novell NetWare® to Windows NT™ Server 4. - Plumley, Sue (New York, United States of América : John Wiley & Sons, Inc., 1997)
"¿How will my files transfer? ¿How do i set up a print server? What kinds of adjustments will my users need to make? ¿Can i compress files in NT? ¿What is a domain? ¿Can i migrate more than one NetWare server at a time? If you're a NetWare network administrator who's considering migrating to Windows NT Server 4, you probably have hundreds of questions like these. In this step-by-step guide, bestselling author Sue Plumley answers all of your most pressing questions. Lear what to do, why you're doing it, and what order to do it in. Build skills and confidence for the inevitable customization work to come. Migrating from Novell NetWare to Windows NT Server 4 gives you technical coverage of Server set-up and administration. You'll get detailed checklists and network diagrams to prepare your system and your users for the new environment." (Copied from the back cover).
Preface. Acknowledgments. Introduction. Part One. Getting started. Chapter 1. Commonly asked questions. Chapter 2. Concepts comparison. Part Two. Understanding NT networks. Chapter 3. Working with users and groups. Chapter 4. Managing security policies. Chapter 5. Managing print services. Part three. Planning and preparing for migration. Chapter 6. Preparing for the migration. Chapter 7. Planning the migration. Part four. Gateway service for netware. Chapter 8. Considerations for using a gateway service. Chapter 9. Using the Gateway service for netware. Part five. Migrating the network. Chapter 10. Using the migration tool with netware. Chapter 11. Running a migration. Chapter 12. Client considerations. Part six. Migrating the network. Chapter 13. Tying up loose ends. Chapter 14. Advanced network management. Chapter 15. Managing multiple domains. Part seven. Preference. Appendix A. Installing Windows NT server and configuring the network. Appendix B. Netware to NT server terms. Appendix C. Glossary. Appendix D. Common problems and solutions. Apendix E. TCP/IP issues. Index.
On the cover: The comprhensive step-by-step guide to preparing your system and users for NT migration.
Keywords: MICROSOFT WINDOWS NT; NETWARE -- COMPUTER FILE; NOVELL NETWARE -- NETWORK OPERATING SYSTEM; WINDOWS NT -- SERVER OPERATING SYSTEM; CLIENT SERVER -- COMPUTING